Synergetic Modeling the Republic of Bashkortostan Energy System Parameters - GAYNANOV, Damir; KANTOR, Olga; KASHIRINA, Ekaterina (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).08, 2017)
The paper presents the results of a synergistic approach to the construction of a model that adequately reflects the ratio of renewable and conventional energy sources in the region’s energy system. The approach uses the methods of the theory of nonlinear dynamic systems. The Lotka – Volterra model was the main used instrument. The calculations allowed investigating the behavior of the Republic of Bashkortostan electric power system with the variation of the initial conditions and to assess the validity of the targets for the share of electricity produced through the use of renewable energy in the total electric power.